2017
DOI: 10.1590/1413-81232017228.21752015
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of n-3 fatty acids in the treatment of hypertriglyceridemia in HIV/AIDS patients: a meta-analysis

Abstract: Effectiveness of n-3 fatty acids in the treatment of hypertriglyceridemia in HIV/AIDS patients: a meta-analysisEfetividade de ácidos graxos n-3 no tratamento da hipertrigliceridemia em pacientes com HIV/AIDS: uma meta-análise 37 97 in Omega 3 groups. The analysis considering trials with more than 1000 mg of EPA/DHA included seven studies and the heterogeneity dropped to 0%.The reduction of combined averages was -101.56mg ). The analysis considering trials with patients that had more than 200 mg/dL of initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Very few studies have investigated the role of n-3 PUFA in PLWH. n-3 PUFA, or fish oil, supplementation has been shown to be beneficial in general for people with hypertriglyceridemia [50] as well as PLWH [51,52]. In the present study, we found that DHA and the ratio of DHA/AA were negatively correlated with baseline CIMT score.…”
Section: Discussionsupporting
confidence: 57%
“…Very few studies have investigated the role of n-3 PUFA in PLWH. n-3 PUFA, or fish oil, supplementation has been shown to be beneficial in general for people with hypertriglyceridemia [50] as well as PLWH [51,52]. In the present study, we found that DHA and the ratio of DHA/AA were negatively correlated with baseline CIMT score.…”
Section: Discussionsupporting
confidence: 57%
“…Fish oils are also known to have beneficial effects in diabetic patients (Pinel et al, 2014). Moreover, fatty acids have been reported to have positive effects in the treatment of patients with AODS (Vieira & Silveira, 2017;Tort et al, 2016). Given the high benefits of consuming seafood in human health, the American Heart Association Nutrition Committee suggests eating fish of 2 or 3 times a week (Kris-Etherton et al, 2003;Mnari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest reduction was seen among people with advanced hypertriglyceridaemia. Numerous studies have shown measurable benefits from incorporating omega-3 supplementation into pharmacotherapy [27] also in the HIV population [25,28,[31][32][33][34]. However, benefits of supplementation have not been established for protease inhibitors [10].…”
Section: Discussionmentioning
confidence: 99%